Efficacy of Magnetic Therapy in Pain Reduction in Patients with Chronic Pelvic Pain: A Systematic Review - De Pedro Negri, Alicia María; Ruiz Prieto, María Jesús; Díaz-Mohedo, Esther; Martín-Valero, Rocío (MPDI, 2022)
Chronic pelvic pain (CPP), also known as chronic pelvic pain syndrome (CPPS), is a common and painful condition. However, its treatment is still a challenge. The findings about the beneficial effects of electromagnetic therapy provide a new, potentially valid, therapeutic alternative for the management of patients with CPP. Objectives: to analyze the efficacy of magnetic field therapy in pain reduction in patients with CPP and for other variables, such as urinary symptoms and quality of life, as well as to review the evidence, in order to establish an action protocol. A qualitative systematic review was carried out, based on the PRISMA protocol and registered in PROSPERO (CRD42022285428). A search was performed in the PubMed, Medline, Scopus, Cochrane, PEDro, BVS, and WOS databases, including those articles in which the patients suffered from CPP; the study variable was pain, and the intervention was based on the application of magnetic fields. Results: Among the 81 articles found, five clinical trials were considered (with an average score of 7.2 in the PEDro scale), with a total of 278 participants, most of whom presented improvements in perceived pain (p ≤ 0.05), as well as in quality of life (p < 0.05) and urinary symptoms (p = 0.05), evaluated through the NIH-CPSI and VAS scales. The therapy was conducted as a monotherapy or in combination with a pharmacological treatment. There was no common protocol among the different articles. Conclusions: Intervention programs through electromagnetic therapy, on their own or with other therapies, can be effective in patients with CPP
Keywords: Dolor pélvico; Magnetic field therapy; Chronic pelvic pain; Pain